2017
DOI: 10.3390/ijerph14060602
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Challenges of Improving Sanitation and Hygiene Outcomes in a Community Based Intervention: A Cross-Sectional Study in Rural Tanzania

Abstract: Good sanitation and clean water are basic human rights yet they remain elusive to many rural communities in Sub-Saharan Africa (SSA). We carried out a cross sectional study to examine the impact of a four-year intervention aimed at improving access to water and sanitation and reducing waterborne disease, especially diarrhea in children under five years old. The study was carried out in April and May 2015 in Busangi, Chela and Ntobo wards of Kahama District of Tanzania. The interventions included education camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…In this study only few households had hand washing facilities near the latrines. This is higher than the finding from EDHS 2016 report of rural areas [5], rural Tanzania [22] and Kenya [23]. This could be due 7 to scarcity of water, lack of awareness about the importance of hand washing.…”
Section: Discussionmentioning
confidence: 59%
“…In this study only few households had hand washing facilities near the latrines. This is higher than the finding from EDHS 2016 report of rural areas [5], rural Tanzania [22] and Kenya [23]. This could be due 7 to scarcity of water, lack of awareness about the importance of hand washing.…”
Section: Discussionmentioning
confidence: 59%
“…Only 40 (15%) of the 267 HHs with latrine and only 5.3% of the total HHs surveyed had handwashing facility, and only one in ten, 10.7%, of the respondents practiced hand washing at critical periods. A similar study from rural HHs of Tanzania reported that only 13.2% of the HHs had handwashing facilities outside latrine [24], and another study in Gedeo Zone, South Ethiopia, showed that handwashing practices at critical periods were reported to be 44.2% [25]. is is an indication that there is lack of integration of health extension programs to enhance the sanitation across the health care tire system.…”
Section: Discussionmentioning
confidence: 99%
“…Although the torrefaction process requires some energy, it is also the most promising technology for organic waste treatment for its highest greenhouse gas mitigation potential [19]. The produced biocoal, especially when pelletized, poses a lower environmental risk during transport, storage, and combustion, in addition to lowering the risks of sanitary and aquatic pollution [20,21]. Therefore, torrefaction could be one of the potential technologies for elephant dung utilization that are sustainable.…”
Section: Introductionmentioning
confidence: 99%